2019
DOI: 10.1080/03057925.2019.1582323
|View full text |Cite
|
Sign up to set email alerts
|

Being and becoming in teacher education: student-teachers’ freedom to learn in a College of Education in Ghana

Abstract: This paper focuses on how people learn to become teachers. It draws on the experiences of student-teachers and tutors at a College of Education in the south of Ghana, who engaged with an iterative data-generation process over one academic year. While increasing attention is given to the learning experiences of children in Sub-Saharan Africa, teachers' learning experiences remain under-explored, underdocumented and under-theorised. It makes an original contribution to the study of preservice teacher education b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 37 publications
0
11
0
1
Order By: Relevance
“…In addition, students gain a more challenging learning experience and improved soft skills. There have been several previous relevant studies related to learning independence (Buckler, 2020;Joseph et al, 2019;Laga et al, 2022;Purwanti, 2021;Sa'diyah et al, 2022;Tjaija, 2022) who found that learning outside of a study program or university encourages students to compete positively for improved academic insight, learning behavior and skills.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, students gain a more challenging learning experience and improved soft skills. There have been several previous relevant studies related to learning independence (Buckler, 2020;Joseph et al, 2019;Laga et al, 2022;Purwanti, 2021;Sa'diyah et al, 2022;Tjaija, 2022) who found that learning outside of a study program or university encourages students to compete positively for improved academic insight, learning behavior and skills.…”
Section: Introductionmentioning
confidence: 99%
“…2. In other publications we describe our conceptual framework for exploring capabilities, aspiration and education through a sociocultural lens in more detail (Buckler, 2019;Chamberlain et al, 2021). 3.…”
Section: Notesmentioning
confidence: 99%
“…This was deliberate: much work on young people's aspirations in similar contexts draws on the perspectives of those already engaged with alternative education, where aspirations are potentially shaped by normative values embedded in the programme. As educators who work within capability frameworks we believe that education is a key component of the freedom necessary to live a life of value (Mkwananzi, 2019;Sen, 1999;Walker & Unterhalter, 2007), but as socioculturalists we acknowledge that education can impose perspectives on what is considered to be a valuable life (Appadurai, 2004;Buckler, 2019). The potential for this is even greater in the international education context we work in: a field powered by donor-funded programmes aligned with the Sustainable Development Goals and other international conventions.…”
Section: Introductionmentioning
confidence: 99%
“…Much of the literature on tutors in Sub-Saharan Africa suggests that they struggle to act agentively. Buckler (2019), for example, describes how tutors at a college in Ghana feel frustrated and insulted by restrictions on their behaviour and teaching. Stories across our collection, however, showcase agentive acts both inside and outside the classroom.…”
Section: Their Sense Of Agencymentioning
confidence: 99%
“…In this paper we draw on excerpts to illustrate professional identity. It offers a specifically Ugandan lens to build on the work of Murphy and Wolfenden (2013), Stutchbury (2019) and Buckler (2019) -all of whom have emphasised the need for more professional dialogue between tutors to support their learning and professional identity development in contexts of policy change. In addition, by using an innovative storytelling methodology it provides deeper insights into tutors' professional lives and how professional learning might be accommodated and supported through -but not exclusively through -OER.…”
Section: Introductionmentioning
confidence: 99%